PENGARUH PENAMBAHAN EKSTRAK DAUN MANGROVE Avicennia marina PADA PAKAN TERHADAP LAJU PERTUMBUHAN DAN TINGKAT PEMANFAATAN PAKAN IKAN NILA SALIN (Oreochromis niloticus) - Linayati, Linayati; Mardiana, Tri Yusufi; Ardana, Abi; Syakirin, Muhammad Bahrus (Jurnal Perikanan Unram, 2024)
The success of tilapia cultivation actitities must be assisted by supporting materials, one of the potential materials in Api-api mangrove leaves. The purpose of the study was to determine the optimal dose and the effect of giving api-api mangrove leaf extract on the growth rate and utilization rate of tilapia feed. The test animal used was saline tilapia with a size of 4-6 cm ± 0.72. The study used a completely randomized design (CRD) method consisting of 4 treatments and 3 replications with additional doses of mangrove leaf extract, namely, 0 ppm/kg feed (A), 150 ppm/kg feed (B), 250 ppm/kg feed (C). ), 350 ppm/ kg feed (D). Parameters observed were SGR, EPP, SR and water quality. Saline tilapia were fed 7% of fish biomass per day and the frequency of feed was 3 times a day for 35 days. The results showed that saline tilapia fed with the addition of mangrove api-api leaf extract 150 ppm/kg feed produced the highest growth rate in treatment B of 4.66%, EPP 80.00%. SR 100%. Water quality temperature 27.3-28.6 0C, pH 5.5-6.3, salinity 14-15 ppt and DO 6.8-7.9 ppm.